An investigation into high school EFL teachers and students' perceptions of teachers' roles and English teaching through metaphor analysis : - Trần, Thị Trúc Hiền (Trường Đại học Cần Thơ, 2017)
Nghiên cứu phân tích nhận định của giáo viên về nghề nghiệp và vai trò của giáo viên tiếng Anh cấp trung học phổ thông.